Molecular classification of breast cancer using IHC markers: experience from a tertiary cancer center in south India - Nawaz P. N., Shoaib; Sebastian, Nikhil; T., Raja; A., Ramya; J., Kumanan; Goswami, Uddiptya; Vedanta; Aishwarya (International Journal of Research in Medical Sciences, 2023)
Background: Breast cancer is a very heterogeneous disease. Molecular or intrinsic subtypes of breast cancer are based on the gene expression profiling. Doing gene expression profiling in each case is practically difficult. So most of the labs depend on immunohistochemistry to classify breast tumors into various molecular-like subtypes. In this study, we have used immune histochemistry to classify tumors into various subtypes. Methods: We have retrospectively collected the data of breast cancer patients treated at Apollo Cancer Center, Chennai, in whom ER, PR, HER 2 Neu and Ki 67 were done, and the data was analyzed. Results: The commonest molecular subtype observed in the present study was Luminal B HER2 positive, constituting 40% of the cases, followed by a HER2 positive (non-luminal) subtype in 20% of cases. The triple negative subtype was the third most frequent, comprising 18% of the cases. The least frequent subtype was Luminal A, seen in only 8% of cases. Conclusions: There is a higher proportion of luminal B HER2 positive and triple negative subtypes in our study population compared to the other studies in published literature. The proportion of luminal A was lesser in our study compared to the literature.